2020
DOI: 10.1073/pnas.1909046117
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the deep replicability of scientific findings using human and artificial intelligence

Abstract: Replicability tests of scientific papers show that the majority of papers fail replication. Moreover, failed papers circulate through the literature as quickly as replicating papers. This dynamic weakens the literature, raises research costs, and demonstrates the need for new approaches for estimating a study’s replicability. Here, we trained an artificial intelligence model to estimate a paper’s replicability using ground truth data on studies that had passed or failed manual replication tests, and then teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 50 publications
2
55
0
Order By: Relevance
“…The results suggest that statistical properties like sample sizes, p-values and effect sizes of the original studies, and whether the effects are main effects or interaction effects are predictive of successful replication (Altmejd et al, 2019). Models trained on the original papers' narrative text performed better than those on reported statistics (Yang et al, 2020). In both studies, the models perform similarly to the prediction markets on the same data.…”
Section: Predicting Replicabilitymentioning
confidence: 84%
See 1 more Smart Citation
“…The results suggest that statistical properties like sample sizes, p-values and effect sizes of the original studies, and whether the effects are main effects or interaction effects are predictive of successful replication (Altmejd et al, 2019). Models trained on the original papers' narrative text performed better than those on reported statistics (Yang et al, 2020). In both studies, the models perform similarly to the prediction markets on the same data.…”
Section: Predicting Replicabilitymentioning
confidence: 84%
“…The results suggest that statistical properties like sample sizes, p-values, and effect sizes of the original studies as well as whether the effects are main effects or interaction effects are predictive of successful replication. Yang et al (2020) also predict replicability with machine learning models, starting with the Open Science Collaboration (2015) as training data, and doing out-of-sample tests on a more extensive set of replications from psychology as well as economics compared to Altmejd et al They compare predictive models trained on either the original papers' narrative (text), reported statistics or both narrative and reported statistics. The model's accuracy is higher when trained on narrative than when trained on reported statistics, and the results also suggest that higher word combinations correlate with replication.…”
Section: Systematic Replicationsmentioning
confidence: 99%
“…The p-values of the findings has been shown to be correlated with the replication outcomes [ 20 , 21 ]. In particular two other replication based forecasting attempts has shown that p-values are informative to a machine learning algorithm [ 33 , 34 ]. We here test this relationship using the pooled market data.…”
Section: Resultsmentioning
confidence: 99%
“…In the latter, participants trade contracts that give a small payoff if and only if the study is replicated and prices are used to derive the likelihood of replicability. Some other studies have fully automated predictions of replicability, such as machine learning techniques [9,10] although such techniques are not considered further in this paper.…”
Section: Previous Approaches To Predicting Replicabilitymentioning
confidence: 99%